The Relationship between Spiritual Intelligence and Emotional Intelligence to Leadership Patterns - Rosyidi, Hamim; Fitriana, Qurrota A'yuni (International Conference on Sustainable Health Promotion, 2018)
A leader does not only require intellectual intelligence. Successful leaders are those who practice spiritual values in the leading process. Emotional intelligence is also a key success factor for a leader in life. The research objective is to examine the relationship between spiritual intelligence and emotional intelligence in explaining leadership patterns. The research subjects were 18 leaders in the Sunan Ampel State Islamic University. The research method was purposive sampling. Hypothesis testing was conducted using multiple regression analysis. The results show that spiritual intelligence has a positive relationship with leadership patterns with a correlation coefficient of 0.745 and an effective contribution of 0.555 or 55.5%. Emotional intelligence also has a positive relationship with leadership patterns with a correlation coefficient of 0.665 with an effective contribution of 0.443 or 44.3%. There is a significant relationship between spiritual intelligence and emotional intelligence simultaneously to leadership patterns as evidenced by a correlation coefficient of 0.746 and an effective contribution of 0.557 or 55.7%.